Preparation method and application of quasi-two-dimensional pure blue-light perovskite thin film
Through the synergistic effect of thermal spin coating and DEPA additives, the problems of slow crystallization speed and uneven crystallization of quasi-two-dimensional perovskite films are solved, and high-quality preparation of quasi-two-dimensional pure blue light perovskite films are achieved, which improves PLQY and optical performance have expanded its application prospects in optoelectronic devices such as PeLEDs.
Patent Information
- Application Number
- CN202411317908.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
Quasi-two-dimensional perovskite faces problems such as low high-photoluminescence quantum yield (PLQY), uneven n-phase distribution, severe non-radiative recombination, unbalanced charge injection and poor conductivity in the field of blue light emission, which limits its in PeLEDs Application prospects.
The preparation method is adopted that synergistically works with DEPA additives. By precisely controlling the process parameters, the rapid and uniform crystallization of quasi-two-dimensional pure blue light perovskite films is achieved, and the photoluminescent quantum yield and optical performance are improved.
It significantly improves the crystallization rate and uniformity of the film, reduces internal defects and phase separation, improves PLQY to 91.4%, optimizes the optical performance and stability of the film, and enhances its application potential in optoelectronic devices such as PeLEDs. .
Smart Images

Figure HDA0005052753580000011 
Figure HDA0005052753580000012 
Figure HDA0005052753580000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of microelectronic devices, and in particular relates to a preparation method and application of a quasi-two-dimensional pure blue light perovskite film. Background Art
[0002] Quasi-two-dimensional perovskite materials stand out for their unique layered structure, which is composed of alternating inorganic layers and long organic chains, forming a fine layout of multiple quantum wells. By regulating its crystallization kinetics, scientists can use simple spin coating technology to prepare quasi-two-dimensional thin films with high luminescence efficiency, and this process does not require complex purification or ligand exchange steps, showing significant advantages over other perovskite materials. Quasi-two-dimensional perovskites have shown extraordinary capabilities in the flexible regulation of physical and optoelectronic properties. The core lies in the precise regulation of the band structure and optoelectronic properties by fine-tuning the number of layers (n value) between the inorganic layer and the organic layer. As the n value increases, the quantum confinement effect gradually weakens, and the band gap of the two-dimensional perovskite also decreases accordingly. This feature opens up a broad space for the customized design of optical properties. Therefore, by precisely controlling the number of layers and components, scientists can flexibly adjust its luminescent wavelength and successfully achieve luminescence of a variety of specific colors, including blue light. It is particularly worth mentioning that the application of quasi-two-dimensional perovskites in the field of blue light emission has made breakthrough progress. For example, the first 2D perovskite blue light perovskite light-emitting diode (PeLEDs) based on the Ruddlesden-Popper (RP) phase, using (PEA)2PbBr4 as the light-emitting layer, successfully emitted 410nm blue light at room temperature. Although the initial efficiency needs to be improved (EQE is only 0.04%), this achievement has laid an important foundation for the development of blue light PeLEDs. Subsequent research has significantly improved the performance of blue light PeLEDs by continuously optimizing material composition and manufacturing processes, bringing it closer to the threshold of commercial application.
[0003] Compared with three-dimensional perovskites, quasi-two-dimensional perovskites show excellent performance in environmental stability. Their outer organic layer acts as a natural barrier, effectively resisting the erosion of water and oxygen, extending the service life of the device and enhancing stability. In addition, combined with packaging technology and interface engineering strategies, their reliability as light-emitting diode materials can be further consolidated. As a leader in the low-dimensional perovskite family, quasi-two-dimensional perovskites have attracted much attention due to their excellent optical properties. Their inherent quantum well structure not only strengthens the light confinement effect, making blue light emission more efficient and stable; at the same time, it also provides the possibility of achieving deeper blue light emission. However, in the pursuit of deep blue light or even pure blue light emission, there are still challenges such as high photoluminescence quantum yield (PLQY), uneven n-phase distribution, severe non-radiative recombination, unbalanced charge injection, and poor conductivity. These problems restrict the application prospects of quasi-two-dimensional perovskites in blue light PeLEDs. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a method for preparing a quasi-two-dimensional pure blue light perovskite film, which achieves rapid and uniform crystallization of the film by precisely controlling the process parameters, thereby ensuring the acquisition of high-quality quasi-two-dimensional perovskite film and thus improving its application performance in optoelectronic devices such as PeLEDs (perovskite light-emitting diodes).
[0005] The present invention also proposes a perovskite light-emitting diode, comprising an anode conductive glass layer, a hole transport layer, an interface modification layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer stacked in sequence, and a quasi-two-dimensional pure blue light perovskite film prepared by the preparation method.
[0006] According to a first aspect of the present invention, a method for preparing a quasi-two-dimensional pure blue light perovskite film is proposed, comprising the following steps:
[0007] S1. In a solution state, cesium bromide, lead bromide, lead chloride, an organic ligand material, formamidine hydrobromide, lithium bromide and a diethylpyrophosphoramide additive are mixed to obtain a perovskite precursor solution;
[0008] S2. coating the perovskite precursor solution on a substrate at 50-80°C.
[0009] According to the embodiment of the first aspect of the present invention, there are at least the following beneficial effects:
[0010] The present invention is an innovative method for synthesizing a quasi-two-dimensional pure blue light perovskite film and a preparation method thereof by using a hot spin coating method. The core of the method is to achieve rapid and uniform crystallization of the film by accurately controlling the process parameters, which is a key prerequisite for ensuring the acquisition of high-quality quasi-two-dimensional perovskite films and thus improving their application performance in optoelectronic devices such as PeLEDs (perovskite light emitting diodes). In the traditional film preparation process, there are often problems such as slow crystallization speed and uneven crystallization, which directly affect the optical properties and stability of the film, thereby limiting its application in high-performance optoelectronic devices. In response to this challenge, the present invention proposes a new strategy for using a hot spin coating method and an additive to synergize, aiming to fundamentally improve the preparation process of a quasi-two-dimensional pure blue light perovskite film. Specifically, the present invention introduces a hot spin coating method, and uses the centrifugal force generated during the rotation process and the heat energy brought by heating to act on the precursor solution together, promoting its rapid and uniform spreading on the substrate, and accelerating the volatilization of the solvent and the crystallization process of the solute. This method can not only significantly improve the crystallization rate of the film, but also effectively reduce the defects and phase separation phenomenon inside the film, thereby ensuring the uniformity and density of the film.
[0011] At the same time, in order to further optimize the crystallization quality of the film, the present invention also innovatively introduces DEPA as an auxiliary means. The addition of the DEPA additive can adjust the viscosity and surface tension of the precursor solution, promote the formation of favorable phases (such as n = 2 phases), and inhibit the growth of low n phases (n = 1) and the generation of non-radiative recombination centers. The synergistic effect of this additive and the hot spin coating method enables more precise crystallization control during the preparation process, thereby preparing a quasi-two-dimensional pure blue light perovskite film with high PLQY (photoluminescence quantum yield).
[0012] In summary, the present invention successfully solves the problems of slow crystallization speed and uneven crystallization in the traditional preparation process by adopting a new strategy of thermal spin coating and additive synergy, and realizes the rapid and uniform crystallization of quasi-two-dimensional pure blue perovskite film. This high-quality film not only has excellent optical properties and stability, but also has broad application prospects, especially in the manufacturing field of optoelectronic devices such as high-performance PeLEDs.
[0013] In some embodiments of the present invention, the molar ratio of the cesium bromide, the lead bromide, the lead chloride, the organic ligand material, the formamidine hydrobromide, the lithium bromide and the diethylpyrophosphoramide is 1.0-1.2:0.5:0.5:1.5:0.15:0.15:0.1-0.01.
[0014] In some embodiments of the present invention, in solution, Pb 2+ The concentration is 0.08~0.2mmol / ml.
[0015] At the above concentration, Pb 2 + Helps to form high-quality perovskite crystals, improve light absorption and electron mobility, and enhance the efficiency of blue light emission.
[0016] In some embodiments of the present invention, the organic ligand material includes at least one of fluorophenethylammonium bromide and phenethylammonium bromide.
[0017] In some embodiments of the present invention, in a solution state, the solvent includes at least one of dimethyl sulfoxide and N,N-dimethylformamide.
[0018] In some embodiments of the present invention, in step S1, the mixing temperature is 30-80°C.
[0019] In some embodiments of the present invention, in step S2, the coating method includes spin coating; the spin coating time is 30 to 200 seconds.
[0020] In some embodiments of the present invention, in step S2, the spin coating time is 60 to 130 seconds.
[0021] In some embodiments of the present invention, in step S2, the rotation speed of the spin coating is 3000-5000 rpm.
[0022] In some embodiments of the present invention, the substrate is a substrate obtained after pre-treatment.
[0023] In some embodiments of the present invention, the pre-treatment step comprises the following steps:
[0024] A1. Cleaning the substrate by immersing the substrate in a cleaning solution and ultrapure water, respectively, and then using ultrasonic waves to clean the substrate;
[0025] A2. Dry the substrate. Place the cleaned substrate on a hot plate or oven at 100-200°C to dry it to ensure that there is no moisture on the entire substrate.
[0026] A3. Surface treatment: plasma clean the dried substrate for 5 to 30 minutes.
[0027] According to a second aspect of the present invention, a perovskite light-emitting diode is proposed, comprising an anode conductive glass layer, a hole transport layer, an interface modification layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer stacked in sequence, wherein the perovskite light-emitting layer is a quasi-two-dimensional pure blue light perovskite film prepared by a preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0029] Figure 1 This is a process diagram of synthesizing a quasi-two-dimensional blue light perovskite film by thermal spin coating in an embodiment;
[0030] Figure 2 PL spectra of Example 1 and Example 2;
[0031] Figure 3 PL spectra of Example 1 and Comparative Example 1;
[0032] Figure 4 PL spectra of Example 1 and Comparative Example 2;
[0033] Figure 5 PL spectra of Example 1 and Comparative Example 3;
[0034] Figure 6 It is the ultraviolet absorption spectra of Example 1 and Example 2;
[0035] Figure 7 The thermal ultraviolet absorption spectra of Example 1 and Comparative Example 1 are shown;
[0036] Figure 8 The UV absorption spectra of Example 1 and Comparative Example 2 are shown in FIG.
[0037] Fig. 9 The UV absorption spectra of Example 1 and Comparative Example 3 are shown;
[0038] Fig.10 PLQY spectra of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3; DETAILED DESCRIPTION
[0039] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0040] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0042] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0043] Example 1
[0044] This embodiment provides a method for preparing a quasi-two-dimensional pure blue light perovskite film, specifically:
[0045] The preparation method of quasi-two-dimensional pure blue perovskite film is as follows:
[0046] S1. Cesium bromide (CsBr), lead bromide (PbBr2), lead chloride (PbCl2), p-fluorophenethylammonium bromide (pF-PEABr), phenethylammonium bromide (PEABr), formamidine hydrobromide (FABr), lithium bromide (LiBr) and diethylpyrophosphoramide (DEPA, CAS: 1068-21-9) were mixed in the ratio of 1:0.5:0.5:0.75:0.75:0.15:0.15:0.05. The solvent of all materials was dimethyl sulfoxide (DMSO). Finally, Pb 2+ The concentration is 0.10mmol / ml. The prepared perovskite precursor solution is placed in a glove box filled with nitrogen and heated on a hot plate at 40℃ for 4 hours in a dark environment;
[0047] S2. Place the surface treated substrate into a glove box filled with inert gas (N2), set the temperature of the heat plate of the glue spreader to 60°C, wait until the heat plate reaches a constant temperature of 60°C, place the substrate on it, and spin coat the configured perovskite precursor on the substrate. The spin coating speed is 5000 rpm, and the hot spin coating time is 120 s. After the rotation is completed, a quasi-two-dimensional pure blue light perovskite film is obtained.
[0048] The substrate in step S2 is a pre-treated substrate, and the processing steps are:
[0049] A1. Clean the substrate by soaking it in a cleaning solution and using ultrasonic cleaning for 60 minutes. Then soak it in ultrapure water and use ultrasonic cleaning for 60 minutes. During this process, the ultrapure water needs to be replaced every 20 minutes to ensure that there is no residual cleaning solution on the substrate.
[0050] A2. Dry the substrate. Place the cleaned substrate on a hot plate at 150°C for drying. The heating time should be no less than 5 minutes to ensure that there is no moisture on the entire substrate.
[0051] A3. Surface treatment: The dried substrate is subjected to plasma cleaning (PLASMA) treatment for 15 minutes.
[0052] Example 2
[0053] The difference between this embodiment and embodiment 1 is that the thermal spin coating time in the perovskite film spin coating process in step S2 is different, specifically, the thermal spin coating time is 60s, and the quasi-two-dimensional pure blue perovskite film is prepared by thermal spin coating, specifically:
[0054] S1. Cesium bromide (CsBr), lead bromide (PbBr2), lead chloride (PbCl2), p-fluorophenethylammonium bromide (pF-PEABr), phenethylammonium bromide (PEABr), formamidine hydrobromide (FABr), lithium bromide (LiBr) and diethylpyrophosphoramide (DEPA, CAS: 1068-21-9) were mixed in the ratio of 1:0.5:0.5:0.75:0.75:0.15:0.15:0.05. The solvent of all materials was dimethyl sulfoxide (DMSO). Finally, Pb 2+ The concentration is 0.10mmol / ml. The prepared perovskite precursor solution is placed in a glove box filled with nitrogen and heated on a hot plate at 40℃ for 4 hours in a dark environment;
[0055] S2. Place the surface treated substrate into a glove box filled with inert gas (N2), set the temperature of the spin coating hot plate of the glue spreader to 60°C, wait until the spin coating hot plate reaches a constant temperature of 60°C, place the substrate on it, and spin coat the configured perovskite precursor on the substrate. The spin coating speed is 5000rpm and the hot spin coating time is 60s. After the rotation is completed, a quasi-two-dimensional pure blue light perovskite film is obtained.
[0056] Example 3
[0057] The difference between this embodiment and embodiment 1 is that the thermal spin coating temperature in the perovskite film spin coating process in step S2 is different, and the specific spin coating temperature is 80° C. The quasi-two-dimensional pure blue perovskite film is prepared by thermal spin coating, specifically:
[0058] S1. Cesium bromide (CsBr), lead bromide (PbBr2), lead chloride (PbCl2), p-fluorophenethylammonium bromide (pF-PEABr), phenethylammonium bromide (PEABr), formamidine hydrobromide (FABr), lithium bromide (LiBr) and diethylpyrophosphoramide (DEPA, CAS: 1068-21-9) were mixed in the ratio of 1:0.5:0.5:0.75:0.75:0.15:0.15:0.05. The solvent of all materials was dimethyl sulfoxide (DMSO). Finally, Pb 2+ The concentration is 0.10mmol / ml. The prepared perovskite precursor solution is placed in a glove box filled with nitrogen and heated on a hot plate at 40℃ for 4 hours in a dark environment;
[0059] S2. Place the surface treated substrate into a glove box filled with inert gas (N2), set the temperature of the spin coating hot plate of the glue homogenizer to 80°C, wait until the spin coating hot plate reaches a constant temperature of 80°C, place the substrate on it, and spin coat the configured perovskite precursor on the substrate. The spin coating speed is 5000rpm, and the hot spin coating time is 120s. After the rotation is completed, a quasi-two-dimensional pure blue light perovskite film is obtained.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that the configuration of the perovskite precursor does not contain DEPA additive. Specifically, CsBr, PbBr2, PbCl2, pF-PEABr, PEABr, FABr, LiBr and DEPA are mixed in the ratio of 1:0.5:0.5:0.75:0.75:0.15:0.15:0, and a quasi-two-dimensional pure blue perovskite film is prepared by thermal spin coating.
[0062] Comparative Example 2
[0063] The difference between this comparative example and Example 1 is that the hot spin coating process is not used in the spin coating process, but the film is prepared by the room temperature spin coating method. Specifically, the heating function of the heat plate of the glue homogenizer spin coating is cancelled, and the spin coating is carried out at room temperature. After the spin coating is completed, it is placed on a 60°C constant temperature hot plate for 120 seconds for annealing treatment to complete the preparation of the quasi-two-dimensional pure blue light perovskite film.
[0064] Comparative Example 3
[0065] The difference between this comparative example and Example 1 is that the configuration of the perovskite precursor does not contain DEPA additives and the perovskite film spin coating process does not use the method of hot spin coating process, but uses room temperature spin coating method to prepare the film. Specifically, CsBr, PbBr2, PbCl2, pF-PEABr, PEABr, FABr, LiBr and DEPA are mixed according to 1:0.5:0.5:0.75:0.75:0.15:0.15:0, and the heating function of the glue homogenizer spin coating hot stage is canceled, and the spin coating is carried out at 30°C. After the spin coating is completed, it is placed on a 60°C constant temperature hot stage and left for 120s for annealing treatment to complete the preparation of the quasi-two-dimensional pure blue light perovskite film.
[0066] Test Case
[0067] Figure 1 This is a process diagram for synthesizing a quasi-two-dimensional blue light perovskite film by thermal spin coating. The specific process is to first heat the spin coating hot plate of the coater to a certain temperature and maintain it, then place the substrate on the spin coating hot plate, then drop the perovskite precursor solution, and finally spin coat the film according to the set parameters. After the spin coating is completed, a quasi-two-dimensional pure blue light perovskite film is obtained.
[0068] Figure 2The photoluminescence (PL) spectra of Example 1 (hot spin coating for 120s + DEPA) and Example 2 (hot spin coating for 60s + DEPA). According to the test results, the PL spectrum of the film obtained by hot spin coating for 120s with a solution containing DEPA additive is 474nm, while the PL spectrum of the film obtained by hot spin coating for 60s with a solution containing DEPA additive is 473nm. By comparison, it was found that: 1. The peak position of the spectrum. In the two embodiments, the PL spectrum peaks of the film are located at 474nm and 473nm, respectively, which shows that although the hot spin coating time is different, the introduction of the DEPA additive has little effect on the luminescent center position of the film, which may mean that DEPA mainly affects the microstructure and light excitation efficiency of the film, rather than directly changing the intrinsic luminescent wavelength of the luminescent material; 2. The difference in PL intensity. The PL intensity of Example 1 (hot spin coating for 120s) is significantly higher than that of Example 2 (hot spin coating for 60s). This result shows that the extended hot spin coating time is beneficial to the optimization of the internal structure of the film, which may promote the orderly arrangement of molecules, reduce defect states, improve the energy transfer efficiency or enhance the recombination efficiency of photogenerated carriers, thereby significantly improving the photoluminescence performance of the film. 3. Improved film quality. The increase in hot spin coating time may make the film more uniform and dense on the substrate, reduce interface defects and holes, all of which are beneficial to improving the overall quality and optical properties of the film. In addition, longer hot spin coating time may also help the DEPA additive to penetrate more fully into the film, interact more extensively with the main perovskite material, and further improve the luminescence properties of the film.
[0069] Figure 3The photoluminescence (PL) spectra of Example 1 (hot spin coating 120s + DEPA) and Comparative Example 1 (hot spin coating 120s). According to the test results, the PL spectrum of the film obtained by hot spin coating 120s for the solution containing DEPA additive is 474nm, while the PL spectrum of the film obtained by hot spin coating 120s for the solution without DEPA additive has multiple (3) emission peaks, and the PL peak intensity is divided into 425nm, 452nm and 467nm from small to large. By comparison, it was found that the film prepared with DEPA additive (Example 1) showed a single and strong PL spectrum peak at 474nm. The appearance of this single peak indicates that the luminescent center inside the film is highly unified and the energy transfer process is efficient and orderly. In contrast, the film without DEPA additive (Comparative Example 1) showed a more complex PL spectral feature, specifically manifested as three obvious emission peaks, located at 425nm, 452nm and 467nm. The presence of these multiple emission peaks usually reflects the presence of multiple luminescent centers or defect states inside the film, which may lead to non-uniformity and reduced efficiency of energy transfer. At the same time, the PL intensity of Example 1 is much greater than the sum of the intensities of each emission peak in Comparative Example 1. This strong contrast not only verifies the outstanding effect of DEPA additives in improving the photoluminescence performance of thin films, but also further illustrates the important role of DEPA additives in promoting the optimization of the internal structure of thin films, reducing defect states, and improving energy transfer efficiency. In addition, the multiple emission peaks that appear in Comparative Example 1 are caused by the lack of DEPA additives. This phenomenon further emphasizes the indispensability of DEPA additives in regulating the luminescence performance of thin films. DEPA additives may improve the microstructure of the film and promote the orderly arrangement of molecules through interaction with the main perovskite material, thereby reducing non-radiative recombination pathways and improving the radiative recombination efficiency, and ultimately achieving a significant improvement in the photoluminescence performance of the film.
[0070] Figure 4The photoluminescence (PL) spectra of Example 1 (hot spin coating 120s + DEPA) and Comparative Example 2 (normal temperature spin coating 120s + DEPA) are shown. According to the test results, the PL spectrum of the thin film obtained by hot spin coating 120s for the solution containing DEPA additive is 474nm, while the PL spectrum of the thin film obtained by normal temperature spin coating has multiple (2) emission peaks, and the PL peak intensity is 424nm and 461nm from small to large. By comparison, it was found that in Example 1, the film treated by hot spin coating technology showed a single and strong PL spectrum peak, and its peak value was located at 474nm. This result shows that the higher temperature during the hot spin coating process may promote the optimization of the internal structure of the film, reduce defects, and enhance the radiation recombination efficiency of photogenerated carriers, resulting in a single and high-intensity luminescence peak. In addition, the DEPA additive may play a more effective role at high temperatures, such as promoting the crystallinity of the material, improving the band structure or reducing non-radiative recombination centers, further enhancing the luminescence performance. In contrast, the film prepared by the room temperature spin coating method in Comparative Example 2 exhibits two relatively obvious PL emission peaks, located at 424nm and 461nm respectively. The presence of these two emission peaks may suggest the presence of multiple luminescence centers or energy transfer processes in the film. Under room temperature spin coating, the crystallinity of the film may be low and the structure is relatively disordered, resulting in different energy level transitions of photogenerated carriers during the recombination process, resulting in a multi-peak phenomenon. At the same time, the effect of the DEPA additive at room temperature may not be as significant as at high temperature, and it fails to completely suppress non-radiative recombination or optimize luminescence properties. By comparing the PL spectra of the two embodiments, it can be clearly seen that the thermal spin coating method not only significantly improves the intensity of the PL spectrum, but also simplifies the spectral morphology, making it appear as a single and high-intensity emission peak. This discovery emphasizes the superiority of thermal spin coating technology in the preparation of high-performance light-emitting films, especially in applications requiring high-purity and high-efficiency light-emitting materials.
[0071] Figure 5The photoluminescence (PL) spectra of Example 1 (hot spin coating 120s + DEPA) and Comparative Example 3 (normal temperature spin coating 120s) are shown. According to the test results, the PL spectrum of the film obtained by hot spin coating 120s for a solution containing DEPA additive is 474nm, while the PL spectrum of the film obtained by normal temperature spin coating for a solution without DEPA additive has multiple (2) emission peaks, and the PL peak intensity is 424nm and 454nm from small to large. By comparison, it is found that in Example 1, the prepared film exhibits a single and high-intensity PL spectrum peak with a peak value at 474nm by combining the hot spin coating technology with the use of DEPA additives. This result fully proves that the synergistic effect of the high temperature conditions and the DEPA additives during the hot spin coating process can significantly optimize the internal structure of the film, reduce defects, and improve the radiative recombination efficiency of photogenerated carriers, thereby achieving high-purity and high-intensity luminescence. The DEPA additive may have a positive effect on the luminescence performance of the film by promoting the crystallization of the material, adjusting the band structure, or inhibiting the non-radiative recombination path. In contrast, the PL spectrum of the film prepared by the room temperature spin coating method without adding the DEPA additive in Comparative Example 3 shows two relatively obvious emission peaks, located at 424nm and 454nm respectively. This shows that under the condition of room temperature spin coating, the crystallinity of the film is low and the structure is relatively disordered, resulting in different energy level transitions of the photogenerated carriers during the recombination process, thereby producing a multi-peak phenomenon. In addition, without the addition of the DEPA additive, it may not be possible to effectively suppress the non-radiative recombination process or optimize the luminescent center, making the luminescence performance of the film relatively weak. By comparing the PL spectra of the two embodiments, it can be clearly seen that the film containing the DEPA additive and prepared by the hot spin coating method has obvious advantages in luminescence performance. Its PL spectrum intensity is significantly higher than that of the film without adding DEPA and using room temperature spin coating, and the spectral morphology is more single, which further confirms the synergistic effect of hot spin coating technology and DEPA additives in improving the luminescence performance of the film. This discovery not only provides an effective technical path for the preparation of high-performance luminescent films, but also provides an important reference for in-depth understanding of the luminescence mechanism of thin films and the mechanism of action of additives.
[0072] Figure 6The UV-visible absorption spectra of Example 1 (hot spin coating for 120s + DEPA) and Example 2 (hot spin coating for 60s + DEPA). According to the test results, both examples show a clear absorption peak at 416nm, which corresponds to a certain specific transition or energy level structure in the material, which can usually be attributed to the transition from the excited state of n=2 to the ground state. However, it is worth noting that the absorption peak intensity of Example 1 (hot spin coating for 120s) is significantly greater than the absorption peak intensity of Example 2 (hot spin coating for 60s). This phenomenon shows that during the hot spin coating process, the extension of the spin coating time has a positive effect on the UV-visible absorption properties of the film. Specifically, a longer spin coating time may help to further optimize the internal structure of the film, such as improving crystallinity, reducing defects, and enhancing the orderly arrangement of molecules, all of which are conducive to enhancing the material's ability to absorb UV-visible light. In addition, the DEPA additive may play a more adequate role under long-term heat treatment, further promoting the film's absorption of light. Therefore, the higher absorption peak intensity in Example 1 not only reflects the film's stronger absorption capacity for ultraviolet and visible light, but also indirectly proves the synergistic effect of the hot spin coating time and the DEPA additive in improving the optical properties of the film. This discovery has important guiding significance for optimizing the film preparation process and improving the optical properties of the material.
[0073] Figure 7 The UV-visible absorption spectra of Example 1 (hot spin coating for 120s + DEPA) and Comparative Example 1 (hot spin coating for 120s) are shown. According to the test results, the film of Example 1 exhibits an obvious single absorption peak at 416nm, which corresponds to the transition from the excited state of n=2 to the ground state. In contrast, the film of Comparative Example 1 exhibits two absorption peaks, located at 388nm (corresponding to the n=1 phase) and 418nm (corresponding to the n=2 phase). This comparison strongly indicates that the presence of the DEPA additive significantly changes the energy level structure and absorption characteristics of the film, especially inhibits the formation of the n=1 phase.
[0074] In quasi-2D perovskites, suppressing the formation of low-n phase (n=1) has many beneficial effects. The following are some of the main ones:
[0075] 1. Improve optical properties: Low n phases (such as n = 1) often have wider band gaps and lower light absorption capacity, which may lead to loss of perovskite material photoelectric conversion efficiency. By inhibiting the generation of these low n phases, the light absorption of perovskite materials can be more concentrated on high n phases (such as n = 2, 3, etc.), which usually have narrower band gaps and stronger light absorption capacity, thereby improving the optical properties and photoelectric conversion efficiency of the material.
[0076] 2. Enhanced stability: The presence of low-n phases may reduce the overall stability of perovskite materials, as they may be more susceptible to phase change or decomposition due to environmental factors (such as humidity, temperature, light, etc.). By inhibiting the generation of low-n phases, the structural stability and environmental tolerance of perovskite materials can be improved, thereby extending their service life.
[0077] 3. Optimizing charge transport: In quasi-two-dimensional perovskites, charge transport is usually carried out between or within layers. The presence of low-n phases may interfere with or hinder the charge transport path, resulting in increased charge recombination and reduced photoelectric conversion efficiency. By inhibiting the generation of low-n phases, the charge transport characteristics of perovskite materials can be optimized, the charge separation and collection efficiency can be improved, and the photoelectric performance can be further improved.
[0078] 4. Promote the formation of high n phase: Inhibiting the formation of low n phase can also promote the formation and growth of high n phase. High n phase usually has better photoelectric performance and higher stability, and is the ideal phase of perovskite materials in photoelectric applications. By optimizing the preparation process and adding appropriate additives (such as DEPA, etc.), effective inhibition of low n phase and selective growth of high n phase can be achieved.
[0079] In addition, it is worth noting that the intensity of the n=2 single absorption peak in Example 1 is significantly greater than the corresponding n=2 absorption peak intensity in Comparative Example 1. This significant difference not only illustrates the contribution of the DEPA additive to enhancing the film's ability to absorb light of a specific wavelength, but also further confirms the effectiveness of the additive in optimizing the film's structure and performance.
[0080] Figure 8The UV-visible absorption spectra of Example 1 (hot spin coating for 120s + DEPA) and Comparative Example 2 (normal temperature spin coating for 120s + DEPA) are shown in Figure 1. According to the test results, both examples show a significant absorption peak at a wavelength of 416nm. This common feature reveals the effective transition of the excited state of n=2 in the material to the ground state, reflecting the specific energy level structure and optical properties inside the material. However, an in-depth analysis of the spectra shows that the absorption peak intensity of Example 1 (hot spin coating for 120s + DEPA) is significantly higher than that of Comparative Example 2 (normal temperature spin coating for 120s + DEPA). This obvious difference is not only a numerical change, but also an intuitive reflection of the effects of the two different preparation processes. Specifically, the hot spin coating method used in Example 1 promotes the uniformity and compactness of the film by heating the substrate during the spin coating process, and may also accelerate the volatilization of the solvent and the reaction rate of the precursor, which is conducive to the formation of a higher quality film structure. This high-quality film structure may have fewer defects, higher crystallinity and stronger intermolecular interactions, thereby improving the material's absorption efficiency of light, and significantly increasing the absorption peak intensity at 416nm. In contrast, although the room temperature spin coating method used in Comparative Example 2 can also form a film, the density and uniformity of the film may be relatively poor due to the slow evaporation of the solvent and insufficient reaction of the precursor due to the lack of heating, and there are more defects and scattering centers. These factors may lead to reduced absorption and transmission efficiency of light in the film, resulting in relatively weak absorption peak intensity. Therefore, this phenomenon fully illustrates the superiority of the thermal spin coating preparation process in improving film quality and optical properties. Through the thermal spin coating method, the film formation process can be more effectively controlled to obtain a higher quality film structure, thereby enhancing the material's absorption capacity for light of a specific wavelength, and providing more excellent performance for applications such as photoelectric conversion.
[0081] Fig. 9The UV-visible absorption spectra of Example 1 (hot spin coating for 120s + DEPA) and Comparative Example 3 (normal temperature spin coating for 120s) are shown. According to the test results, the film of Example 1 presents a clear and strong single absorption peak at 416nm. This characteristic peak clearly points to the effective transition of the excited state of n=2 to the ground state, reflecting the highly ordered energy level structure and optimized optical properties inside the film. This result not only verifies the effectiveness of hot spin coating combined with DEPA additives in promoting the formation of specific phases (such as n=2 phases), but also demonstrates the significant advantages of this process in improving the purity of the film and reducing impurity phases (such as n=1 phases). In contrast, the film of Comparative Example 3 presents two absorption peaks, located at 388nm and 418nm, respectively, corresponding to the transitions of n=1 phase and n=2 phase, respectively. This double peak phenomenon indicates that under normal temperature spin coating conditions, n=1 phase and n=2 phase coexist in the film. This may be due to factors such as the slow solvent evaporation rate and incomplete precursor reaction during room temperature spin coating, which makes the phase structure of the film not uniform enough, thus affecting its optical properties. It is worth noting that the absorption peak intensity of n=2 in Example 1 is significantly greater than the corresponding n=2 absorption peak intensity in Comparative Example 3. This significant difference not only illustrates the advantages of the thermal spin coating process in improving film quality and purity, but also highlights the important role of DEPA additives in promoting the formation and stabilization of n=2 phases. Thermal spin coating accelerates the volatilization of solvents and the reaction rate of precursors by providing additional thermal energy, which is conducive to the formation of a more dense and uniform film structure; and the DEPA additive may further promote the formation and stabilization of the n=2 phase by adjusting the reaction path of the precursor or enhancing the interaction between molecules.
[0082] Fig.10The photoluminescence quantum yield (PLQY) spectra of Example 1 (hot spin coating 120s + DEPA), Comparative Example 1 (hot spin coating 120s), Comparative Example 2 (normal temperature spin coating 120s + DEPA) and Comparative Example 3 (normal temperature spin coating 120s) are shown. According to the experimental results, it can be clearly seen that the PLQY of the film (Example 1) containing a DEPA additive solution and prepared by hot spin coating is as high as 91.4%, which is significantly better than the other three groups of experiments. In contrast, the PLQY of the film (Comparative Example 1) prepared by hot spin coating without using DEPA additive is 70.7%. Although it also shows a high photoluminescence efficiency, it is significantly lower than that of Example 1. This comparison strongly illustrates the key role of DEPA additives in improving the PLQY of perovskite films. Further analysis shows that the PLQY of the film prepared by room temperature spin coating is significantly lower than that of the film prepared by hot spin coating, regardless of whether it contains DEPA additives. Specifically, the PLQY of the film containing DEPA additive and prepared by room temperature spin coating (Comparative Example 2) is 64.6%, while the PLQY of the room temperature spin coating film without DEPA additive (Comparative Example 3) is as low as 23.7%. This result not only proves the superiority of thermal spin coating in improving film crystallinity, reducing defects and improving photoluminescence efficiency, but also further emphasizes the positive role of DEPA additive in promoting this process. In summary, Fig.10 The experimental results clearly show that the perovskite film prepared by hot spin coating is significantly better than the film prepared by room temperature spin coating in terms of PLQY. This is mainly attributed to the fact that the additional heat energy provided by hot spin coating helps to promote the full reaction of the precursor and the rapid volatilization of the solvent, thereby forming a more dense, uniform and less defective film structure. In addition, the addition of DEPA additive further improves the photoluminescence efficiency of the film, which may be due to the important role of DEPA in promoting the formation of specific phases (such as n = 2 phase), inhibiting the growth of low n phase (n = 1) and the generation of non-radiative recombination centers, and improving the surface morphology of the film. Therefore, the preparation process of hot spin coating combined with DEPA additive provides an effective and feasible way to prepare high-performance perovskite films.
[0083] In summary, the film containing DEPA additive and prepared by hot spin coating has obvious advantages in luminescence performance. Its PL spectrum intensity is significantly higher than that of the film without DEPA added and spin-coated at room temperature, and the spectral morphology is more single, which confirms the synergistic effect of hot spin coating technology and DEPA additive in improving the luminescence performance of the film. This discovery not only provides an effective technical path for the preparation of high-performance luminescent films, but also provides an important reference for in-depth understanding of the luminescence mechanism of thin films and the mechanism of action of additives, and optimizes the morphology and crystallinity of the film: the additional heat energy provided during the hot spin coating process helps to promote the full reaction of the precursor and the rapid volatilization of the solvent, thereby forming a more dense, uniform and less defective film structure. The addition of DEPA additives may further promote the formation of high n phase (n = 2 phase) and inhibit the growth of low n phase (n = 1) and the generation of non-radiative recombination centers, thereby improving the overall quality of the film. Improve the photoluminescence quantum yield (PLQY): The PLQY of the quasi-two-dimensional perovskite film prepared by thermal spin coating and adding DEPA additive is as high as 91.4%, which is significantly higher than other films that do not use DEPA or use room temperature spin coating. High PLQY means that more photons can be effectively emitted, which is crucial for improving the luminescence efficiency and performance of optoelectronic devices (such as LEDs).
[0084] The above content describes the embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing a quasi-two-dimensional pure blue light perovskite film, characterized in that: The following steps are involved: S1. In a solution state, cesium bromide, lead bromide, lead chloride, an organic ligand material, formamidine hydrobromide, lithium bromide and a diethylpyrophosphoramide additive are mixed to obtain a perovskite precursor solution; S2. coating the perovskite precursor solution on a substrate at 50-80°C.
2. The preparation method according to claim 1, characterized in that: In terms of molar ratio, the cesium bromide, the lead bromide, the lead chloride, the organic ligand material, the formamidine hydrobromide, the lithium bromide and the diethylpyrophosphoramide are 1.0-1.2:0.5:0.5:1.5:0.15:0.15:0.1-0.
01.
3. The preparation method according to claim 1, characterized in that: In solution, Pb 2+ The concentration is 0.08~0.2mmol / ml.
4. The preparation method according to claim 1, characterized in that: The organic ligand material includes at least one of fluorophenethylammonium bromide and phenethylammonium bromide.
5. The preparation method according to claim 1, characterized in that: In a solution state, the solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone and N,N-dimethylpropylene urea.
6. The preparation method according to claim 1, characterized in that: In step S1, the mixing temperature is 30-80°C.
7. The preparation method according to claim 1, characterized in that: In step S2, the coating method includes spin coating; the spin coating time is 30 to 200 seconds.
8. The preparation method according to claim 7, characterized in that: In step S2, the spin coating time is 60 to 130 seconds.
9. The preparation method according to claim 7, characterized in that: In step S2, the rotation speed of the spin coating is 3000-5000 rpm.
10. A perovskite light-emitting diode, characterized in that: The invention comprises an anode conductive glass layer, a hole transport layer, an interface modification layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer which are stacked in sequence, wherein the perovskite light-emitting layer is a quasi-two-dimensional pure blue light perovskite film prepared by the preparation method according to any one of claims 1 to 9.